2007
DOI: 10.2478/s11686-007-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gyrodactylus ectoparasites in Polish salmonid farms by PCR-RFLP of the nuclear ITS segment of ribosomal DNA (Monogenea, Gyrodactylidae)

Abstract: The Gyrodactylus fauna of 274 fish taken from ten salmonid farms in Poland was sampled in 2006. Four fish species were investigated: rainbow trout Oncorhynchus mykiss, brown trout Salmo trutta (morphs fario, lacustris, and trutta), grayling Thymallus thymallus and huchen Hucho hucho. No parasites were observed on huchen. No indications of gyrodactylosis were observed, but an unexpected parasite species diversity was found. A molecular species identification by polymerase chain reaction (PCR) and restriction fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 58 publications
2
45
0
Order By: Relevance
“…skin scrapes), the likelihood of G. truttae occurring on stock held at the other farms cannot be ruled out. Gyrodactylus teuchis has previously been reported in France, sporadically in Denmark and the UK and appears to be common on rainbow trout in Polish fish farms (Lautraite et al, 1999;Cunningham et al, 2001;Rokicka et al, 2007). Lautraite et al (1999) found G. teuchis to be widely distributed on both wild and farmed salmonids from Brittany to the Western Pyré né es, and the current survey now extends its distribution into Italy.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…skin scrapes), the likelihood of G. truttae occurring on stock held at the other farms cannot be ruled out. Gyrodactylus teuchis has previously been reported in France, sporadically in Denmark and the UK and appears to be common on rainbow trout in Polish fish farms (Lautraite et al, 1999;Cunningham et al, 2001;Rokicka et al, 2007). Lautraite et al (1999) found G. teuchis to be widely distributed on both wild and farmed salmonids from Brittany to the Western Pyré né es, and the current survey now extends its distribution into Italy.…”
Section: Discussionmentioning
confidence: 81%
“…This survey together with recent studies on gyrodactylids in rainbow trout farms in Europe (e.g. Rokicka et al, 2007;Dzika et al, 2009) points to the importance of this industry for spreading of G. salaris in Europe. It seems more than likely that the examination of rainbow trout farms in other countries will extend the range further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining parts of the parasite´s bodies were stored in absolute ethanol SPECTRANAL (Allied-Signal, Riedel-de Haën). The specimens collected in Sudan were placed directly in absolute ethanol and the slides for morphological analysis were subsequently prepared in the home laboratory according to the methods previously used by Rokicka et al (2007).…”
Section: Methodsmentioning
confidence: 99%
“…The DNA was eluted in 50 μl. The Internal Transcribed Spacer (ITS) region of the ribosomal DNA was amplified with ITS1F (5'-GTTTCCGTAGGTGAACCT-3') (Rokicka et al 2007) and ITS2R (5'-TCCTCCGCTTAGTGATA-3') (Matějusová et al 2001), and a partial fragment of 18S was amplified using primers S1 (5'-ATTCCGATAACGAACGAGACT-3'), which anneal in the internal region of the 18S gene (Sinnappah et al 2001) and ITSR3A (5'-GAGCCGAGTGATCCACC-3') (Matějusová et al 2001), in a Mastercycler eP gradient (Eppendorf).…”
Section: Methodsmentioning
confidence: 99%